2021
DOI: 10.1002/smll.202006786
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Machine Learning‐Based Clustering of Nanosized Fluorescent Extracellular Vesicles

Abstract: Extracellular vesicles (EV) are biological nanoparticles that play an important role in cell‐to‐cell communication. The phenotypic profile of EV populations is a promising reporter of disease, with direct clinical diagnostic relevance. Yet, robust methods for quantifying the biomarker content of EV have been critically lacking, and require a single‐particle approach due to their inherent heterogeneous nature. Here, multicolor single‐molecule burst analysis microscopy is used to detect multiple biomarkers prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Among CD81 + EVs, we found that 67% (64.3%–69.8%) of EVs coexpressed another copy of CD81 that could be labeled with a fluorophore-conjugated antibody. Consistent with the observation of others, we found heterogeneity among EVs’ surface protein “pan-EV” markers even though they were derived from the same cell line. ,, We chose to use CD81 for capture and labeling, rather than neuron specific surface markers, because this protein could be characterized using established Nanoview assay kits, allowing us to quantify and benchmark the performance of DEVA. Improving the performance of DEVA assay required optimization in a multidimensional parameter space, including the concentration of several reagents and blocking conditions.…”
Section: Development and Characterization Of Assay Conditions For Ult...supporting
confidence: 79%
“…Among CD81 + EVs, we found that 67% (64.3%–69.8%) of EVs coexpressed another copy of CD81 that could be labeled with a fluorophore-conjugated antibody. Consistent with the observation of others, we found heterogeneity among EVs’ surface protein “pan-EV” markers even though they were derived from the same cell line. ,, We chose to use CD81 for capture and labeling, rather than neuron specific surface markers, because this protein could be characterized using established Nanoview assay kits, allowing us to quantify and benchmark the performance of DEVA. Improving the performance of DEVA assay required optimization in a multidimensional parameter space, including the concentration of several reagents and blocking conditions.…”
Section: Development and Characterization Of Assay Conditions For Ult...supporting
confidence: 79%
“…Multidimensional single burst analysis spectroscopy combining with t-SNE is a powerful tool to multidimensional characterize single EVs with high accuracy and speed, which will significantly improve the diagnostic ability of EV in disease-related biomarker studies. [283] Similarly, Yan et al described a platform based on SERS in combination with multivariate analysis to characterize single exosomes derived from different biological sources (Figure 13a). The Raman substrate was made of a graphene-covered Au surface containing quasi-periodic pyramidal arrays.…”
Section: Artificial Intelligence In Single Evs Characterizationmentioning
confidence: 99%
“…Recent studies have employed machine learning in different stages of development of EV based therapeutics including identification of EVs [166] and single EV analysis. [167][168][169] Use of above mentioned high throughput techniques such as microfluidics in combination with machine learning based EV analysis could accelerate the clinical translation of EV-based therapeutics.…”
Section: Outlook and Future Perspectivesmentioning
confidence: 99%